Pendidikan Untuk Pengembangan Karakter (Telaah terhadap Gagasan Thomas Lickona dalam Educating For Character) - Dalmeri Dalmeri (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
This paper discusses about Thomas Lickona’s idea on education character. It is mainly an attempt to shape one's personality through education which it results can be seen in action in the form of one's good behavior, honest, responsible, respect the rights of others, hard work, and so on. The main goal of educational character is to encourage good habits; so that, learners understand, able to feel, and want to do goods. Educational character has the same mission with behavior education or moral education. Thomas Lickona assert that the basic laws of morality should be applied in the educational sectors in accordance with the principles of religious teachings in the holy scriptures. Therefore, the implications of the basic laws of morality will be universally valid.